Managing information technology outsourcing - Beulen, Erik; Ribbers, Pieter (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"For decades, outsourcing has been a major international phenomenon in business. The areas of Technology, Information Technology and Management represent a unique case for outsourcing both in terms of benefits and potential interorganisational problems. This fully updated text has been brought up to date with this new landscape, including discussion of Robotic Process Automation, Internet of Things, cloud computing, low code and DevOps and agile. With a range of new global case studies in manufacturing, logistics, chemical industry and cloud services, this textbook offers a strong grounding in real-world industrial experience that effectively combines theory with practice. Uniquely, this book focuses on both sides of the outsourcing relationship, providing a balanced exploration of the ways in which these partnerships can be managed successfully. Accessible and cutting-edge, the third edition of Managing Information Technology Outsourcing provides an in-depth, practical perspective on this important and far-reaching challenge in information technology management. It is an ideal text for students, academics and practitioners alike"--
Market Trends in Information Technology Outsourcing -- Theoretical Foundation -- Changing Business Models -- IT Strategy and IT Outsourcing -- IT Services: Demand and Supply -- Information Technology Innovation and Outsourcing -- Transitions and Contracts -- Governance of IT Outsourcing -- Governance Factors -- Contracting and Managing Agile Software Development and DevOps -- Compliance -- Looking Forward.
OCLC-licensed vendor bibliographic record.
Keywords: Information technology -- Management; Contracting out; Electronic data processing departments -- Contracting out; BUSINESS & ECONOMICS / Information Management; BUSINESS & ECONOMICS / Production & Operations Management